POTRET SEKOLAH SD MARGINAL POKJAR CERDAS I DI KECAMATAN TENAYAN RAYA KELURAHAN SAIL KOTA PEKANBARU - ", Yuliana; ", Yoserizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research was conducted in SD Marginal Pokjar Cerdas 1 in Kecamatan Tenayan Raya Kelurhan Sail Kota Pekanbaru. The formulation of the problem are (1) how is the representation of pokjar cerdas 1 as a marginal school (2) what is the effort of school to keep the process of teaching and learning. The purpose of research (1) to know the reresentatin of pokjar cerdas 1 as a marginal school (2) to know the effort of school to keep the process of teaching and learning. This research was qualitative description research. The sample of this research were five people. The technique of research was purpose sampling. The instrument of data were observation, interview and documentation of this marginal school was categorized as quite feasible for the process teaching and learning because the building was only 100 Ã— 100 m and the area of SD Marginal 300 m. Althought the building was permanent but still a marginal status. There are 3 classes and in the classroom there are double classes. frist grade and second grade, third grade and fourth grade, fifth grade and sixth grade. The marginal school still used parallel class or double classes. The condition of the road to the marginal school was very slippery nd muddy when it rains. Thus interferingthe KBM process. The location of thr marginal school farfrom pekanbaru center 30 km. the salaries of the tearchers arepaid by the provincial education office.Keyword: School, SD Marginal, Intelligent Pokjar I